PURPLE SWEET POTATO (Ipomoea batatas L.) PEELS EXTRACT AS AN ALTERNATIVE DYE FOR BACTERIA GRAM STAINING - Nastasya Nunki; Diah Titik Mutiarawati; Endah Prayekti (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2020)
Crystal violet and Safranin are dyes in Gram staining, which are carcinogenic. Alternative safe materials are needed to minimize the use of carcinogenic properties. Purple sweet potato (Ipomoea batatas L.) peels were the candidate of the alternative dye source because of its high anthocyanin pigment. The purpose of this study was to determine purple sweet potato (Ipomoea batatas L.) peels extract as an alternative to Gentian violet in Gram staining of bacteria. Extracts obtained from purple sweet potato peels studied with varying concentrations of 50%, 60%, and 75% for 1, 3, and 5 min as a substitute for Gentian violet on Bacillus sp. The parameters observed from this study based on visual field clarity, glass slide cleanliness, contrast, bacterial shape, bacterial colour. Each extract concentration compared with a control group using Gentian violet. The results showed that optimum staining in 50% concentration for 5 min, 60% concentration for 5 min, 75% concentration for 3 min, and 5 min respectively. The present study exhibited the potency of Ipomoea batatas L. peels extract as an alternative staining agent.